2016
DOI: 10.4236/oalib.1102021
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Bedene Alemtena Small Scale Irrigation Scheme in Hallaba Special Woreda, Southern Ethiopia

Abstract: The aim of study was to assess the overall performance of Bedene Alemtena small scale irrigation scheme using internal and external performance indicators. Primary data were collected from three farmers' field situated at the upper, middle, and downstream of the main canal. Discharge measurements and soil sample analysis were conducted, and secondary data were collected from Halaba Kullito Bureau of Agriculture. CROPWAT 8.0 computer model was used to calculate the crop water requirements. From the analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The current finding revealed that distribution uniformity was above sufficient, in which 30 and 65% were taken as poor and sufficient, respectively [24]. Similar findings were reported by many authors, which the water distribution uniformity was greater than 90 % [17,21,25,26]. However, Dinka [27] also reported conflicting results that average water distribution uniformity of the Ketar medium Scale irrigation Scheme was 61.6% due to the scheme operating at flow rates below or above the design flow rates.…”
Section: Water Distribution Uniformity (Du)supporting
confidence: 88%
“…The current finding revealed that distribution uniformity was above sufficient, in which 30 and 65% were taken as poor and sufficient, respectively [24]. Similar findings were reported by many authors, which the water distribution uniformity was greater than 90 % [17,21,25,26]. However, Dinka [27] also reported conflicting results that average water distribution uniformity of the Ketar medium Scale irrigation Scheme was 61.6% due to the scheme operating at flow rates below or above the design flow rates.…”
Section: Water Distribution Uniformity (Du)supporting
confidence: 88%
“…Several internal and external performance indicators were mentioned by Molden et al (1998) to assess the performance of irrigation schemes. From the internal indicators, storage, application and conveyance efficiency were selected to evaluate the scheme's performance (De Alwis & Wijesekera, 2011; Dessalew et al, 2016; Kartal et al, 2020). Similarly, agricultural, water supply, physical and financial performance indicators were selected from the external indicators based on Değirmenci et al (2017), Agide Dejen (2012), Bumbudsanpharoke and Prajamwong (2015) and Al‐Said et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…It was intended to serve around 157 households found in Boneya Molo Kebele. The conveyance system of the irrigation scheme consists of a Main canal (MC) taking water from the corresponding intake of the weir [10][11][12]. The main canal starts from the water abstraction site on the side of the weir and conveys water for a length of 2535 m of the main canal, for the first 2500 m it is a lined canal and for the rest, it is an unlined canal.…”
Section: Diversion Headwork Structuresmentioning
confidence: 99%
“…The model needs climatic information, such as the mean monthly precipitation, minimum and maximum temperature ( o c), relative humidity (%), wind speed (km/day), and sunshine hours (hr), to calculate the reference evapotranspiration (ETO) value. After estimating effective rainfall using the USDA Soil Conservation Service (SCS) method, the determination of IWR was carried out [12].…”
Section: Determination Of Cwr and Iwrmentioning
confidence: 99%